ANAMOSTIC LEXICAL METHODOLOGY FOR PHILOSOPHY STUDENTS - Mamatkulova Bakhtijon Ravshanovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The article explores the methodological foundations of applying anamostic lexical methodology in teaching English to philosophy students. Anamostic lexical methodology focuses on the study of naming, conceptualization, and lexical meaning within philosophical discourse. This approach integrates linguistic, cognitive, and cultural aspects of language, allowing learners to understand how philosophical concepts are expressed and interpreted through specific lexical structures. The study emphasizes the importance of linking philosophical terminology with linguistic awareness to enhance critical thinking, interpretation, and academic writing skills among philosophy students.